Atividades práticas nas aulas de ciências: um estudo sobre a ação docente nos anos finais do ensino fundamental - Souza, Sandra Aparecida de Oliveira e (2017)
Practical activities may contribute in an engaging and meaningful way to effectiveness in the process of teaching and learning Science. Therefore, this present study aims to analyze how the Science teachers devise the usage of practical activities in their classes, which strategies, spaces and resources they apply, and the challenges they experience in developing the practical activities in the final years of elementary school. In order to accomplish this research, we determined a qualitative research (a case study, particularly)which we accompanied, by means of classes observation and semi-structured interviews, the work of four Science teachers from a full-time public school, located in the city of São Paulo. To support this research, we elected a literary review that assembles the teaching of Sciences in a historical and social perspective, under the perception of Krasilchik (2000, 2008, 2012), Delizoicov, Angotti and Pernambuco (2011); the training and the teaching practice in the area of Sciences, according to the studies of Carvalho and Gil-Pérez(2011), Cachapuz, Praia and Jorge (2002, 2002a, 2004), Pozo and Crespo (2009), Bizzo (2002, 2005);and the researchers Hodson (1998), Leite (2000) and Dourado (2001) as a reference on the concept of practical activities. The acquired results demonstrated that, according to those teachers, practical activities are important to stimulate observation and curiosity, allowing greater understanding of content and improvement in scientific learning. The reported data also indicated that, unlike other surveys with the same profile, this school relies on some essential conditions to obtain satisfactory results in the development of these activities: teacher education; constant pedagogical monitoring; exchange of experiences between peers; continuous planning and adequate infrastructure. Such acknowledgments suggest that discussions about the extension of the school day and its reflection on teacher training and practice should be expanded, and, consequently, improving the quality of Science teaching.